ANALISIS PERSPEKTIF HUKUM PIDANA INTERNASIONAL BAGI WARGA UIGHUR ATAS KEJAHATAN GENOSIDA YANG DILAKUKAN OLEH CHINA MENURUT STATUTA ROMA - Antoni Herli; Arsysta Indry; Rahma Anisa; Zilvania Sofi; Rahman Nur (Jurnal De Jure Muhammadiyah Cirebon, 2022)
In this writing, the author wants to analyze the crime of genocide committed by China against the Uighurs in the perspective of international criminal law and according to the Rome Statute. one of which was later included in the 1998 Rome Statute. The Chinese government has been accused of crimes against humanity and genocide against ethnic Uighurs in Xinjiang where at least one million Uighurs have been detained in the region and detained in extra-judicial camps or sent to prison. China has deliberately made a systematic, integrated policy with the so-called 'optimizing' population of the Xinjiang population, which is essentially aimed at reducing the Uighur population and the populations of other ethnic minorities in the long term which is achieved by limiting and reducing the birth of ethnic Uighurs.